Cabaran dan Elemen Kearifan Tempatan dalam Pensijilan Halal di Malaysia: The Challenges and Elements of Local Wisdom in Malaysia Halal Certification - Pauzi, Norhidayah binti; Man, Saadan (Jurnal Fiqh, 2019)
Malaysia has conducted various halal programs such as organizing the Malaysia International Halal Showcase (MIHAS), developing the International Halal Park Malaysia (MIHAP) and establishing halal hubs at the state level which have boosted Malaysia's position as the leader and centre of the international halal sector, which thus, has greatly contributed to the enhancement of Islamic economy worldwide. Halal certification is not only focused on food and beverage products but it comprehensively includes all aspects of human life such as finance, logistics, tourism, cosmetics and pharmaceuticals. The development of Malaysia's halal industry in its own criteria has proven that it is a type of Malaysian local wisdom. This article aims to highlight the historical aspects of halal certification development in Malaysia and the elements of local wisdom by reviewing its successful contribution to the halal industry of the country as well as identifying the challenges. This article is based on library research which mainly rely on the documentation process by gathering data from primary sources and secondary sources such as books, journal articles and papers. Field studies were also conducted to obtain data from selected informants from the JAKIM Halal Hub Division. The findings show that the development and criteria of the Malaysian halal certification is mainly based on the values and rulings of the Shafii madhhab, i.e. the madhhab that has long been practiced by Malaysian Muslims since the early days. The Shafii madhhab has been a major reference in halal standards developed by the Department of Standards, the Manual Procedure for Malaysia Halal Certification provided by JAKIM and the national fatwa. This is due to the stronghold of the Malay community to the Shafii madhhab in their everyday life.